Clinical Findings and Genetic Expression Profiling of Three Pigmented Lesions of the Optic Nerve - Manuel A. de Alba; Victor M. Villegas; Aaron S. Gold; Andrea Wildner; Fiona J. Ehlies; Azeema Latiff; Timothy G. Murray (Case Reports in Ophthalmological Medicine)
Background. Optic disk melanocytoma is a primary tumor of the optic disk that represents a clinical diagnostic challenge due to its similarities with melanoma. Purpose. The authors present three cases in which genetic expression profiling was used to identify tumor prognosis of optic disk melanocytoma. Case Series. In two cases fine-needle aspiration biopsy was performed to obtain tissue through a transvitreal route into the apex of the tumor while the patient underwent pars plana vitrectomy, laser ablation, phacoemulsification with posterior chamber intraocular lens implantation, and intravitreal triamcinolone acetonide. In the other case the tissue was obtained after definite enucleation. Conclusion. Genetic expression profiling is a useful diagnostic tool for classification and can provide vital information to the ocular oncologist regarding prognosis.